Living with and dying from advanced heart failure: understanding the needs of older patients at the end of life - Klindtworth, Katharina; Oster, Peter; Hager, Klaus; Krause, Olaf; Bleidorn, Jutta; Schneider, Nils (BMC geriatrics, 2015)
Heart failure (HF) is a life-limiting illness and patients with advanced heart failure often suffer from severe physical and psychosocial symptoms. Particularly in older patients, HF often occurs in conjunction with other chronic diseases, resulting in complex co-morbidity. This study aims to understand how old and very old patients with advanced HF perceive their disease and to identify their medical, psychosocial and information needs, focusing on the last phase of life.